Green Procurement Practices in enchancing Envirmental Waste Management. A Case Study of Taka Taka Plastics Company - Moise Kituka Mpibwe (Uganda Christian University, 2024)
The study investigated the role of green procurement practices in enhancing environmental waste management in private organizations a case study of Taka Taka Plastics Company. With increasing global and regional attention on sustainable procurement, the research objectives aimed to assess how supplier environmental performance, sustainable product selection, and eco-conscious procurement policies influenced waste management outcomes in private organizations. A cross-sectional research design was employed, integrating both quantitative and qualitative approaches to gather comprehensive data. The study focused on employees from various departments within the organization, with a sample size determined using the Yamane formula. Data collection involved structured questionnaires and in-depth interviews targeting key informants. A mixed-method approach ensured balanced representation through random and purposive sampling techniques. The research adhered to ethical considerations, including informed consent and participant confidentiality. The analysis revealed a predominantly male participant group with diverse educational backgrounds and age distribution with significant representation from the Production and Procurement departments. The study revealed a strong emphasis on environmental compliance, waste reduction initiatives, and renewable energy usage among suppliers. The survey results highlighted the importance of formal green procurement policies, regular updates, and employee training in enhancing environmental waste management Key findings revealed a strong emphasis on environmental compliance, waste reduction initiatives, and renewable energy usage among suppliers. Eco-conscious procurement policies markedly influenced decision-making processes, highlighting the importance of formal green procurement policies, regular updates, and employee training in enhancing environmental waste management. The investigation also indicated that while many organizations possessed formal green procurement policies, there was a clear need for improvement in policy integration and enforcement. Recommendations included increased budget allocation for sustainable products, stricter procurement criteria, reduced packaging waste, and the incorporation of life-cycle assessments into procurement processes, underscoring the necessity for continuous review and enhanced staff involvement to promote sustainability efforts.